The body of war : media, ethnicity, and gender in the break-up of Yugoslavia - Žarkov, Dubravka, 1958- (Next wave (Duke University Press), 2007)
Examines how notions of femininity and masculinity and heterosexual norms produced ethnicity in the disintegration of former Yugoslavia and also looks at how words and images created by the media are just as influential as violent practices in constructin.